2020
DOI: 10.9734/jamb/2020/v20i930281
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Resistance Pattern of Candida Species Isolated from High Vaginal Swabs of Women Attending a Hospital in Enugu State, Nigeria

Abstract: There is an increase in non-albicans Candida (NAC) vulvovaginal candidiasis which is attributed to overuse of antifungal therapy and this has led to antifungal resistance. This study was aimed at determining the antifungal resistance pattern of some clinical isolates of Candida species. Eighty-eight (88) isolates were used which included Candida tropicalis (34), Candida Parapsilosis (21), Candida albicans (20), Candida krusei (7) and Candida glabrata (6). The drugs used were Fluconazole (25µg), Ketoconazole (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…10 In the current study, Candida species isolated were C. tropicalis 34 (68%) C. albicans 12(24%) and C. parapsilosis 4 (08%) from various specimens, this has the same pattern as the studies conducted elsewhere. 11,12 The resistance pattern for the Candida species shows that C. tropicalis isolates showed 12% resistance to fluconazole and 6% to amphotericin B. The study by Urvashi et al showed that there was 59% and 9.4% resistance for C. tropicalis against fluconazole and amphotericin B which is slightly higher than our study.…”
Section: Discussioncontrasting
confidence: 68%
“…10 In the current study, Candida species isolated were C. tropicalis 34 (68%) C. albicans 12(24%) and C. parapsilosis 4 (08%) from various specimens, this has the same pattern as the studies conducted elsewhere. 11,12 The resistance pattern for the Candida species shows that C. tropicalis isolates showed 12% resistance to fluconazole and 6% to amphotericin B. The study by Urvashi et al showed that there was 59% and 9.4% resistance for C. tropicalis against fluconazole and amphotericin B which is slightly higher than our study.…”
Section: Discussioncontrasting
confidence: 68%
“…On the other hand, the increase in their incidence could be attributable to the selection pressure exerted by the increasingly increasing use of azoles in the treatment of certains cancers and vaginal candidiasis. [28]. The increase in non-albicans Candida species should raise fears of an increasingly frequent occurrence of recurrent vaginal candidiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Candida is an opportunistic normal flora of the human reproductive and gastrointestinal mucosa and may be isolated from the mouth, vagina, gut, and throat [1]. The transition from a harmless commensal to a disease causing pathogen depends on the immune system of the host and virulence factors of the Candida species [2].…”
Section: Introductionmentioning
confidence: 99%
“…More than 90% of immunocompromised persons, which are HIV patients, present with oral candidiasis [3]. Seventy-five percent of women experience a Candida infection at least once in their lifetime [1] and this could result in systemic infections that are fatal to pregnant women and critically unwell patients with a fatality rate of approximately 30% [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation